Formación en hábitos educativos para el subnivel Básica Superior. - Gallardo Bustillos, Iván Patricio (2020)
The researching job is based on the study of upper basic level student´s habits that have been instilled in educational institutions since the first school years, however, factual reality has shown that they have mostly left to train habits for academic activities, or put them into practice but poorly. It is intended to encourage the students about the significant usages involved in studying tasks, so that their effort is more rational, conscious and they feel greatfully with their performance. The main objective is to develop a methodological strategy for training the student´s habits related with the intercultural education system, taking into account the overall conditions of their social development. Chapter 1 contains the epistemological foundation related to the topic, chapter 2 establishes the methodological proposal with elements, and chapter 3 develops the proposal validation and results visualization. This researching job has a qualitative approach, and a certain quantitative implication; it uses both an observation file and a survey, that were aimed at students at eighth, ninth and tenth years students of fiscal education institution “Edmundo Carbo”. The studying is concluded from experts and users validations. The survey has been adapted to the need for this investigation of the Study Habits Inventory, to evaluate studying habits.